Analysis of the Word Nadhir in the Qur'an - Rahma Azizi Meliasani; Wahyu Nur Sinta Sari; Sekar Galuh Putri Wiseno; Nadia Alisyia Nuri (Bulletin of Islamic Research, 2023)
This study addresses a research gap in the linguistic and semantic analysis of the word "nadhir" in the Qur'an. While previous research has explored the term's theological implications, there is limited comprehensive analysis of its lexical, syntactic, and contextual variations across different Qur'anic verses. This research employs a linguistic approach, focusing on lexicon and syntax to examine the usage of "nadhir" in the Qur'an. The study systematically analyzes key Qur'anic verses using interpretative frameworks from classical and modern tafsir (exegesis). The findings reveal that the word "nadhir" functions in multiple capacities: as a divine warning of punishment, a reminder of moral accountability, and a call for spiritual vigilance. The analysis also underscores the connection between "nadhir" and the prophetic mission, highlighting its role in communicating divine mercy and justice. Furthermore, the research identifies variations in how the term is framed grammatically and semantically within different contexts, enhancing the understanding of its multifaceted role in Islamic discourse. The study's significance lies in its contribution to Qur'anic linguistic studies by providing a systematic examination of the word "nadhir". It enriches the academic discourse on Qur'anic semantics and offers insights relevant to contemporary da'wah practices. This research also lays the foundation for future interdisciplinary studies exploring the intersection of linguistics, theology, and religious communication.